Changes following supplementation with lutein and zeaxanthin in retinal function in eyes with early age-related macular degeneration: a randomised, double-blind, placebo-controlled trial. Issue 3 (16th September 2014) - Huang, Yang-Mu; Dou, Hong-Liang; Huang, Fei-Fei; Xu, Xian-Rong; Zou, Zhi-Yong; Lu, Xin-Rong; Lin, Xiao-Ming
Abstract : Aims: To investigate functional and macular pigment (MP) changes in patients with early age-related macular degeneration (AMD) after multiple supplementation with lutein and zeaxanthin. Methods: 112 patients with early AMD were randomly (1:1:1:1) assigned to receive 10 mg lutein, 20 mg lutein, lutein (10 mg)+zeaxanthin (10 mg), or placebo daily for 2 years. MP optical density (MPOD) was recorded at baseline, 48 weeks and 2 years. Retinal sensitivities were measured by multifocal electroretinogram for peak-to-trough amplitude (N1P1) at baseline and at 48 weeks, and in terms of microperimeter-determined mean retinal sensitivity (MRS) at 48 weeks and 2 years. Results: Supplementation with lutein and zeaxanthin augmented MPOD significantly in active treatment groups (all p<0.05). N1P1 response densities showed significant increases in ring 1 and ring 2 after 48 weeks of supplementation, while no significant changes were seen in rings 3–6. Significant increases in MRS were detected after supplementation with either 10 or 20 mg lutein, whereas no such increases were seen in the placebo arm. Conclusions: Supplementation with lutein and/or zeaxanthin increases MPOD, and supplemental lutein enhances retinal sensitivity, in patients with early AMD. Trial registration number: Clinicaltrials.gov NCT10528605 .